1994
DOI: 10.1177/0893318994007003002
|View full text |Cite
|
Sign up to set email alerts
|

Group Performance in Computer-Mediated and Face-to-Face Communication Media

Abstract: This study explores the effects of computer-mediated communication (CMC) and face-to-face (FTF) media on group performance under four experimental conditions. There were CMC-only, FTF-only, FTF/CMC, and CMC/FTF groups. The study examined three variables: the number of unique ideas generated, the time to reach consensus, and the decision quality. Vigilant interaction theory was helpful in exploring the media effects on group performance. Results indicate that, in general, CMC groups generate a greater number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 26 publications
1
54
0
Order By: Relevance
“…The variety of ideas makes the groups' work more focused on solving the problem rather than defending a solution. Olaniran (1994) observed that using electronic brainstorming produces significantly more fresh ideas. The use of the EMS allows the calculation of data to be produced by the system and the results are available throughout the meeting as well as in the summary at the end of the session.…”
Section: The Advantages Of Using the Emsmentioning
confidence: 99%
“…The variety of ideas makes the groups' work more focused on solving the problem rather than defending a solution. Olaniran (1994) observed that using electronic brainstorming produces significantly more fresh ideas. The use of the EMS allows the calculation of data to be produced by the system and the results are available throughout the meeting as well as in the summary at the end of the session.…”
Section: The Advantages Of Using the Emsmentioning
confidence: 99%
“…Similarly, the theme for the inaugural 2016 High-Level Political Forum (HLPF) for the SDGs held from 11-20 July 2016 was "Ensuring that No One is Left Behind." The overall theme for Habit III, scheduled for Quito, Ecuador from [17][18][19][20] October is the New Urban Agenda. Finally, the focus of the WSIS+10 Outcome Document is the use of the Internet and ICTs to support the implementation of the new Sustainable Development Agenda.…”
Section: Introductionmentioning
confidence: 99%
“…Consensus-making and/or dissensus-avoiding are chiefly operationalized in group decision support system (GDSS) research as dependent variables occurring primarily at the end of a communicative experience (e.g., Olaniran 1994;Valacich et al 1994). In the realm of face-to-face dialogue, Fishkin (see Fishkin and Rosell 2004;Fishkin 2009) has utilized structured, deliberative focus group techniques to expose randomly selected members of the public who are ''uninformed about key issues'' to ''carefully balanced briefing materials'' (Fishkin 2009, p. 1), resulting in ''dramatic, statistically significant changes in views'' (p. 3)-essentially generating stronger consensuses (and, in some cases, dissensuses).…”
Section: Introductionmentioning
confidence: 99%